The History of Norway.. - Dagre, Tor (1999)
The first men to appear in what is now Norway, emerged from dim prehistory when the great inland ice sheets were retreating over Scandinavia. 10,000 years ago the forefathers of today's Norwegians hunted reindeer and other prey on their long trek north. The land they came to had for centuries borne the weight of the icecap, so the coastline was about 200 metres higher than it is today. The oldest proofs of human activity were discovered on a hill in the southeast region of Østfold, not far from the southern frontier with Sweden. At that time the hill was probably an offshore island, just south of the glacier tip.